Assessment of Noise Pollution Behbahan City, Iran - Mehrjo, Farzad; Zaron, Ali Bozorgi; Nejatolahi, Mohammad (Kathmandu University Journal of Science, Engineering and Technology, 2013)
Noise pollution in urban areas of many countries in the world is a widespread problem and now worldwide recognizes it as a major problem for the quality of life in urban areas. Road traffic, industrial and production units and construction machinery are the causes of urban noise pollution. Behbahan city is one of the most populous Khuzestan cities in Iran. Assessment of noise pollution in Behbahan city was performed by seven stations as indicators and a station as a witness of commercial-residential areas. The Testo 815 Sound level meters device was used for data collection. Collecting data started from 20 February 2010 for duration of 28 circadian by the stations. Standard sound of commercial-residential zone in the open air Iran, for day time and night time are 60 dB and 50 dB respectively. Compared to the noise measurement in studied stations in Behbahan city we could say that Behbahan has noise pollution problem. Noise pollution can be due to high traffic volume, the width of streets, cars, motorcycles and distance disregard between commercial-residential areas and noise pollution sources noted.